PERAN ZAKAT PRODUKTIF DALAM PENINGKATAN EKONOMI UMAT (STUDI PERBANDINGAN PEMIKIRAN MASDAR FARID MAS'UDI DAN DIDIN HAFIDUDDIN) - Sugiono, Sugiono; Huda, Nurul (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2025)
The distribution of zakat today is no longer limited to providing basic necessities or consumptive needs for mustahik. Zakat can now also be distributed in the form of productive zakat. Zakat itself is an obligation for every Muslim, and it is an act of worship that concerns both the relationship between humans and fellow humans, as well as the relationship between a servant and Allah SWT. The distribution of productive zakat plays a significant role in promoting justice and reducing poverty. This is achieved through activities such as skills training, assistance in acquiring work tools, and business capital support. Ultimately, this approach is expected to contribute to the overall economic growth of society, particularly in improving the economic well-being of mustahik. Currently, in Indonesia, there are government zakat agencies as well as non-governmental organizations tasked with collecting and distributing zakat funds. Didin Hafiduddin, in his book, argues that zakat management should be carried out by zakat management institutions that are established and authorized by the government, and therefore possess formal legal authority. Meanwhile, according to Masdar Farid Mas‘udi, the management of zakat should be handed over directly to the state.Considering the importance of zakat in efforts to optimize its utilization, as well as the differences in perspectives on who is entitled and responsible for its management, it is necessary to conduct an in-depth study to ensure better zakat management in the future. This research is a descriptive-comparative analysis using content analysis techniques. The data collection method in this study is mainly based on literature review, drawing from books and writings by Didin Hafiduddin and Masdar Farid Mas‘udi, as well as from research or studies related to the thoughts of key figures or the utilization of productive zakat and its impact on the welfare and economic improvement of mustahik.Keywords: Zakat Fund, Productive Zakat; mustahik; muzakki; literature study